Correction: Nakkala et al. Differential Regulation of DC Function, Adaptive Immunity, and MyD88 Dependence by Two Squalene Emulsion-Based Vaccine Adjuvants. Vaccines 2024, 12, 531 - Jayachandra Reddy Nakkala; Yibo Li; Labone Akter; Xinliang Kang; Xinyuan Chen (Vaccines)
The authors would like to make the corrections described below to the published paper [...]